이산화탄소 해양지중저장 처리를 위한 파이프라인 수송시스템의 열-유동 해석 - 허철(CHEOL HUH); 강성길(SEONG-GIL KANG); 홍섭(SUP HONG); 최종수(JONG-SU CHOI); 백종화(JONG-HWA BAEK) (Han-guk haeyang gonghak hoeji (Online), 2008)
The concentration of atmospheric carbon dioxide (CO2), which is one of the major greenhouse gases, continues to rise with the increase in fossil fuel consumption. In order to mitigate global warming the amount of CO2 discharge to the atmosphere must be reduced. Carbon dioxide capture and storage (CCS) technology is now regarded as one of the most promising options. To complete the carbon cycle in a CCS system, a huge amount of captured CO2 from major point sources such as power plantsshould be transported for storage into the marine or ground geological structures. Since 2005, we have developed technologies for marine geological storage of CO2,including possible storage site surveys and basic design of CO2 transport and storage process. In this paper, the design parameters which will be useful to construct on-shore and off-shore CO2 transport systems are deduced and analyzed. To carry out this parametric study, we suggested variations in thedesign parameters such as flow rate, diameter, temperature and pressure, based on a hypothetical scenario. We also studied the fluid flow behavior and thermal characteristics in a pipeline transport system.